Biomagnification of Some Heavy and Essential Metals in Sediments, Fishes and Crayfish from Ondo State Coastal Region, Nigeria - Asaolu, S. S.; Olaofe, O. (Biological Sciences - PJSIR, 2005)
The biomagnification levels of some essential (Fe, Zn, Cu) and toxic metals (Pb, Ni, Cd, Cr, Co, Mn) were determined in sediments, three kinds of fish (Oreochromis niloticus, Synodonthis sp., and Clarias gariepinus), and cray- fish from the Ondo State coastal region. The metal biomagnification in the fish and crayfish was several times greater than in water, while that in the sediments was several thousand-folds greater than in both the organisms and water. Among the metals examined in water, Fe was the most abundant with average values of 146.7 and 74.3 mg/l, respectively, for wet and dry seasons, while Co was the least with average values of 2.4 and 1.6 mg/l. In the sediments, concentrations of Pb, Ni, Fe, Cr, Co and Mn in the wet season were relatively higher than those obtained for the dry season. Fe with an average of 50.9 mg/kg in C. gariepinus was the most abundant metal in the fish samples, while Cu with an average value of 0.3 mg/kg in niloticus was the least. The metal biomagnification for most of the metals for both seasons was found to vary widely from one location to the other. This was confirmed by the coefficient of variation that ranged from 31% to 144% and 29% to 130% in the wet and dry seasons, respectively. The present study has shown that fish, crayfish and sediments can be used to monitor the pollution level of metals in the Nigerian coastal water.